Tim-3 Is Differentially Expressed during Cell Activation and Interacts with the LSP-1 Protein in Human Macrophages - Ranferi Ocaña-Guzman; Lucero A. Ramon-Luing; Luis A. Vazquez-Bolaños; Michelle Rodríguez-Alvarado; Fausi Bulhusen-Rodriguez; Alonso Torres-Hatem; Karen Gonzalez-Torres; Mariana Citlalli de Alba-Alvarado; Isabel Sada-Ovalle (Journal of Immunology Research, 2023)
T-cell Immunoglobulin and Mucin Domain 3 (TIM-3) is an immune checkpoint receptor known to regulate T-cell activation and has been targeted for immunotherapy in cancer and other diseases. However, its expression and function in other cell types, such as macrophages, are poorly understood. This study investigated TIM-3 expression in human macrophages polarized to M1 (stimulated with IFN-γ and LPS) and M2 (stimulated with IL-4 and IL-13) phenotypes using an in vitro model. Our results show that M1 macrophages have a lower frequency of TIM-3+ cells compared to M2 macrophages at 48 and 72 hr poststimulation. Additionally, we observed differential levels of soluble ADAM 10, an enzyme responsible for TIM-3 release, in the supernatants of M1 and M2 macrophages at 72 hr. We also found that the TIM-3 intracellular tail might associate with lymphocyte-specific protein 1 (LSP-1), a protein implicated in cell motility and podosome formation. These findings enhance our understanding of TIM-3 function in myeloid cells such as macrophages and may inform the development of immunotherapies with reduced immune-related adverse effects.